2005
DOI: 10.1097/01.tp.0000149501.50870.9d
|View full text |Cite
|
Sign up to set email alerts
|

Positron-Emission Tomography Imaging of Early Events after Transplantation of Islets of Langerhans

Abstract: The aim of our study was to assess cell trafficking and early events after intraportal islet transplantation. Sprague-Dawley rat islets were incubated for various times, with various concentrations of 2-[F]fluoro-2deoxy-D-glucose (FDG), and in presence of various glucose concentrations. FDG-labeled syngeneic islets or FDG alone were injected in rats. Radioactivity was measured in the liver and in various organs by positron-emission tomography for 6 hours. FDG uptake increased with incubation time or FDG concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 11 publications
(11 reference statements)
0
55
0
Order By: Relevance
“…In a syngeneic rat model of IPIT, an average of 43% of the infused tracer radioactivity was found in the liver 1 h after islet transplantation (Toso et al, 2005). Based on these and other observations, the authors suggested that inflammatory events immediately following IPIT (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…In a syngeneic rat model of IPIT, an average of 43% of the infused tracer radioactivity was found in the liver 1 h after islet transplantation (Toso et al, 2005). Based on these and other observations, the authors suggested that inflammatory events immediately following IPIT (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, taking advantage of bicarbonate and/or organic anion transporters expressed by pancreatic acinar cells, [ 11 C]acetate has been used to visualize the exocrine pancreas [6,7]. In addition, animal studies show that 2-[ 18 F]fluoro-2-deoxy-D-glucose may be useful in imaging recently transplanted islets [8]. Markmann et al [9] recently reported that transplanted cadaveric islets, 14 months posttransplantation, induce peri-islet cell mass fat deposits that are visible by chemical shift gradient-echo magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…However, with repeated transplantations or larger graft volumes, a temporary rise in portal venous pressure (11), accompanied by a reduction in portal blood flow and increase in liver enzymes (12), has been found. (13)(14)(15) [ 18 (16,17).…”
Section: Islet Transplantation Is a Treatment Option For Selected Patmentioning
confidence: 99%